2021
DOI: 10.1186/s13613-021-00904-7
|View full text |Cite
|
Sign up to set email alerts
|

High risk of patient self-inflicted lung injury in COVID-19 with frequently encountered spontaneous breathing patterns: a computational modelling study

Abstract: Background There is on-going controversy regarding the potential for increased respiratory effort to generate patient self-inflicted lung injury (P-SILI) in spontaneously breathing patients with COVID-19 acute hypoxaemic respiratory failure. However, direct clinical evidence linking increased inspiratory effort to lung injury is scarce. We adapted a computational simulator of cardiopulmonary pathophysiology to quantify the mechanical forces that could lead to P-SILI at different levels of respi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 60 publications
0
60
0
Order By: Relevance
“…There is a concern regarding self-inflicted lung injury from the sustained high respiratory effort in spontaneously breathing patients [29]. A computational modeling study showed that the forces generated by increased inspiratory effort in acute hypoxic respiratory failure from COVID-19 are comparable to those involved in ventilator-induced lung injury [30]. Therefore, further prospective studies are needed to determine whether late failure causes diffuse alveolar damage.…”
Section: Discussionmentioning
confidence: 99%
“…There is a concern regarding self-inflicted lung injury from the sustained high respiratory effort in spontaneously breathing patients [29]. A computational modeling study showed that the forces generated by increased inspiratory effort in acute hypoxic respiratory failure from COVID-19 are comparable to those involved in ventilator-induced lung injury [30]. Therefore, further prospective studies are needed to determine whether late failure causes diffuse alveolar damage.…”
Section: Discussionmentioning
confidence: 99%
“…They found that elevated pixel values of DRRS were more frequent in COVID-19 patients as compared to healthy controls. As COVID-19 patients may be at increased risk for developing P-SILI [13], these data indicate that DRRS could prove to be a useful marker for early recognition of potentially injurious spontaneous efforts.…”
mentioning
confidence: 84%
“…A recently published study demonstrated that the median oesophageal pressure swing in non-COVID-19 patients with moderate or severe respiratory failure undergoing noninvasive ventilation trial was 34 cmH 2 O [ 72 ]. Although these phenomena have been identified in respiratory failure from any aetiology [ 74 , 75 ], including experimental lung oedema [ 76 ], modelling of data clearly shows that the forces generated by increased inspiratory effort are seen in COVID-19 are significant and compatible with the development of P-SILI [ 77 ]. Large inspiratory efforts – particularly when persisting despite noninvasive ventilation - are harbinger of physiological deterioration, failure of noninvasive support and need for invasive mechanical ventilation [ 72 ].…”
Section: Compensations To Chemical and Mechanical Stimuli: Respiratory Drive Effort And Dyspnoeamentioning
confidence: 99%